Prevalence of elimination stomas in a microregion in the north of Minas Gerais (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: To estimate the prevalence of people with elimination stoma and to characterize them for sociodemographic and clinical aspects. Method: A descriptive cross-sectional study with a sample of 27 patients with elimination stomas residing in a microregion in the north of Minas Gerais, who met the inclusion criteria. The data collected were recorded in an instrument used in previous studies and analyzed using descriptive statistics. Study approved by the Ethics Committee. Results: The prevalence of people with stoma was 2.16/10.000, the sample contained 55.6% of men, 40.7% were married, mean age 59.1 years, 59.2% were literate and 74.0% had low income; 59.3% of the stomas were cancerous, more frequent colon and rectum tumours, 70.4% of the stomas were definitive, and 74.0% were colostomies. Dermatitis was the main complication and 68.2% of the patients presented effluent of pasty consistency and performed self-care. Conclusion: The prevalence of people with stoma was like that of other municipalities in Minas Gerais and below that expected by the National and International Ostomized Associations. The characterization of the people, of the stomas and the management of these, will contribute for health professionals and managers to review the assistance protocols used in the studied microregion.